Prevalence of unexpected red blood cell antibodies in pregnant women and follow-up of pregnancy outcome in pregnant women treated with intra-uterine transfusion - Sunil Golia; Aseem Kumar Tiwari; Geet Aggarwal; Anil Khetrapal; Sandeep Kumar Tyagi; Chetna Jain; Shubham Gupta; Samruddhi Pawar (Asian Journal of Transfusion Science)
BACKGROUND: For the management of hemolytic disease of the fetus and newborn (HDFN), it is important to detect unexpected red cell antibody in pregnant women. We assessed the prevalence of unexpected red cell antibodies in consecutive pregnant women attending antenatal clinic (ANC). More importantly, cases with unexpected antibody causing severe anemia were followed-up for intervention (Intra-uterine transfusion IUT) and outcome of pregnancy (still-birth/live-healthy). AIMS AND OBJECTIVES: The study was conducted with an objective to find the prevalence of unexpected RBC antibodies in pregnant women, their specificity and to do the follow-up for IUT and outcome of pregnancy (still-birth, live-birth) in antibody positive women. MATERIALS AND METHODS: This was a prospective study from January 2021 to May 2022 at two tertiary care centres. All antenatal samples received by the laboratory were screened for unexpected red cell antibody. Whenever antibody screen was positive, antibody identification was performed. Patients, positive for unexpected antibody and anemia were followed up for any transfusion-based intervention and outcome of pregnancy. RESULTS: A total of 539 consecutive samples were worked up and among these, 10 samples (1.85%) were found to be antibody positive. The antibodies identified were Anti-D (n=6), anti-Leb (n=1), anti-M (n=1), anti-C (n=1) and anti-E (n=1).The prevalence of unexpected antibodies in Rh positive and Rh negative pregnant women was 0.83% and 10.9% respectively. Follow-up was done for all 10 cases with unexpected antibody and anemia was monitored by MCA PSV (middle cerebral artery peak systolic velocity).Two women developed severe anemia thus requiring single intrauterine transfusion (at 26 weeks and 28 weeks respectively) each, for correction of anemia. In both these cases, healthy male child was delivered. At 3-month follow-up both children were alive and healthy. CONCLUSION: The study found prevalence of unexpected RBC antibodies in pregnant women as 1.85%. The study also underlined importance of transfusion-based interventions contributing to successful outcome in couple of cases with severe anemia.